MENGELOLA LAPORAN KEUANGAN PARA PELAKU USAHA PADA PKBM BINA MANDIRI BANDUNG - Dini Wahjoe Hapsari; Dudi Pratomo; Elly Suryani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Every business people is required to make a financial report which is the accountability report of his business activities. Including a newly business people. They are required to prepare financial statements without being trapped in the complexity of the applicable accounting standards. These business people can arrange financial statements simply as long as they do not deviate from the applicable standards.To be able to manage financial statements, at the beginning of this business people must know the type of business, opportunities and challenges in the business world. When they understand their business position, they must make an analysis so that their business runs well. After finding new positions and business opportunities, business people can determine strategies in making financial statements so they are easy to use.Many business people today have not done business analysis and bookkeeping properly, so they do not have the required financial statements. This is due to the lack of understanding of business people how to manage financial reports in the business they are running.This community service activity provides training for business people at the Bina Mandiri Community Learning Center (PKBM) located on Jalan Tubagus Ismail No. 27 Bandung. The method used is to provide material, questions and answers and discussions that discuss the problems faced and suggestions for solutions. Provide financial report templates that can be used by participants. The activity was ended by filling out a questionnaire related to the activity which was the feedback of the activity. Based on the results of the questionnaire, it can be seen the achievements of the activities and expectations of the participants in the future.Training on the management of financial statements is very beneficial for participants, they become more aware of the importance of preparing financial reports and the function of financial statements. Participants hope there will be more training with different material tailored to the problems expressed